Ecological stoichiometry, salt ions and homeostasis characteristics of different types of halophytes and soils - Zhao, Yinghan; Li, Tian; Liu, Junhan; Sun, Jingkuan; Zhang, Ping (Frontiers in Plant Science, 2022)
Studying eco-stoichiometric and salt ions characteristics of halophytes and soils is helpful to understand the distribution mechanism of nutrients and salts in halophytes and their adaptation strategies to salinized habitats. In this study, three different types of halophytes (Phragmites communis-salt repellent, Suaeda salsa-salt accumulating, and Aeluropus sinensis- salt secreting) and soils were selected to analyze the differences and correlations of C, N, P stoichiometry and salt accumulation. Results showed that: (1) the total nitrogen (TN) and total phosphorus (TP) contents of the three halophytes' leaves were significantly higher than those of the roots and stems, and the C: N ratios were contrary to the difference mentioned above. The growth of P. communis and S. salsa was mainly limited by P, A. sinensis was limited by N and P. S. salsa had a stronger absorption capacity for Na+ and Mg2+ . The interrelationship between salt ions and C, N and P ecological stoichiometry of halophyte organs was influenced by the type of halophytes. (2) The TC, TN, and N: P contents of the three halophyte communities in the surface soil (0-20 cm) were significantly higher than the other soil layers, while P did not differ significantly among soil layers. The planting of different halophytes affected the TC, TN, C: N, N: P values and the content of seven ions in the surface soil. SO42-was positively correlated with soil TC, TN, N:P, and Na+ were positively correlated with soil TC in three halophytes. (3) The P. communis TC and A. sinensis TN contents were negatively correlated with soil TC, TN, C: P, and N: P, whereas TC contents of S. salsa were positively correlated with the aforementioned soil indicators. The P. communis and A. sinensis TC contents were negatively correlated with soil K+, while this correlation was opposite between S. salsa and soil. (4) The homeostasis of C, N, and P elements in all three halophytes showed that C > N > P, the homeostasis was strongest in A. sinensis and weakest in S. salsa. The results provide theoretical basis for the restoration of saline land in the Yellow River Delta.